The male of Mischocyttarus nomurae Richards, with a re-examination of the limits and contents of the M. cerberus species group (Hymenoptera, Vespidae, Polistinae, Mischocyttarini) - Silveira,Orlando Tobias (2004)
The male of Mischocyttarus nomurae Richards, 1978 is described for the first time, and relationships between this and other similar species are discussed in a context of redefining the limits of the M. cerberus species group.